2024
DOI: 10.1021/acsaem.3c02589
|View full text |Cite
|
Sign up to set email alerts
|

oCVD PEDOT-Cl Thin Film Fabricated by SbCl5 Oxidant as the Hole Transport Layer to Enhance the Perovskite Solar Cell Device Stability

Kafil Chowdhury,
Sanjay K. Behura,
Mohammad Rahimi
et al.

Abstract: Perovskite solar cells (PSCs) exhibit remarkable power conversion efficiency (PCE) but face limitations due to poor stability, restricting their practical applications. The commonly used hole transport layer, poly(3,4-ethylene dioxythiophene):polystyrenesulfonate (PEDOT:PSS), suffers from inherent acidity that compromises PSCs device stability through detrimental interactions with the counter electrode and perovskite layer. This study explores the use of oxidative chemical vapor deposition (oCVD) with antimony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…37 Post-deposition rinsing with methanol or acids can remove both residual oxidants and unreacted monomers in oCVD thin films and therefore improve their electrical properties. 29,32 Another potential improvement may involve the use of liquid oxidants, such as antimony pentachloride (SbCl 5 ), 38,39 in replacement of solid oxidants like FeCl 3 whose by-products are well known to remain in the oCVD thin films. 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Post-deposition rinsing with methanol or acids can remove both residual oxidants and unreacted monomers in oCVD thin films and therefore improve their electrical properties. 29,32 Another potential improvement may involve the use of liquid oxidants, such as antimony pentachloride (SbCl 5 ), 38,39 in replacement of solid oxidants like FeCl 3 whose by-products are well known to remain in the oCVD thin films. 37…”
Section: Resultsmentioning
confidence: 99%
“…31–33 Such a feature was previously exploited to increase the lifetime of electronically excited states, 34 and enhance the sensing 35 and catalytic properties 36 of conjugated polymer thin films prepared via the oCVD of polycyclic aromatic compounds. Upon reaction with a suitable oxidizing agent, 29,37–39 both simple electron-rich monoaromatic compounds 30,32,38,40 and polycyclic aromatic compounds 31,34–36,39 can be polymerized via oCVD. A recent report has demonstrated that conjugated polymer thin films can even be grown from electron-poor aromatic compounds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Improving competitiveness and sustainability in all industry sectors, including semiconductor manufacturing, is crucial for securing market share and ensuring business success. This is particularly evident in semiconductor manufacturing, which utilizes various chemical vapor deposition (CVD) methods [9][10][11] for both inorganic semiconductors [9,12] and organic conducting polymers [11,[13][14][15][16][17][18] across a wide range of electronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%